Bi‐allelic mutations in HARS1 severely impair histidyl‐tRNA synthetase expression and enzymatic activity causing a novel multisystem ataxic syndrome. Issue 7 (29th April 2020) - Galatolo, Daniele; Kuo, Molly E.; Mullen, Patrick; Meyer‐Schuman, Rebecca; Doccini, Stefano; Battini, Roberta; Lieto, Maria; Tessa, Alessandra; Filla, Alessandro; Francklyn, Christopher; Antonellis, Anthony; Santorelli, Filippo M.
Abstract: Mutations in histidyl‐tRNA synthetase (HARS1), an enzyme that charges transfer RNA with the amino acid histidine in the cytoplasm, have only been associated to date with autosomal recessive Usher syndrome type III and autosomal dominant Charcot–Marie–Tooth disease type 2W. Using massive parallel sequencing, we identified bi‐allelic HARS1 variants in a child (c.616G>T, p.Asp206Tyr and c.730delG, p.Val244Cysfs*6) and in two sisters (c.1393A>C, p.Ile465Leu and c.910_912dupTTG, p.Leu305dup), all characterized by a multisystem ataxic syndrome. All mutations are rare, segregate with the disease, and are predicted to have a significant effect on protein function. Functional studies helped to substantiate their disease‐related roles. Indeed, yeast complementation assays showing that one out of two mutations in each patient is loss‐of‐function, and the reduction of messenger RNA and protein levels and enzymatic activity in patient's skin‐derived fibroblasts, together support the pathogenicity of the identified HARS1 variants in the patient phenotypes. Thus, our efforts expand the allelic and clinical spectrum of HARS1‐related disease.